Arnau de Villanova, De parte operativa, edición de Fernando SALMÓN y Michael R. McVAUGH, en Michael R. McVaugh, Fernando Salmón, Sebastià Giralt y Jon Arrizabalaga (eds.), Arnaldi de Villanova Opera Medica Omnia VIII, Barcelona, Fundació Noguera-Universi (Minerva. Revista de Filología Clásica, 2024)
Reseña de Arnau de Villanova, De parte operativa, edición de Fernando Salmón y Michael R. McVaugh, en Michael R. McVaugh, Fernando Salmón, Sebastià Giralt y Jon Arrizabalaga (eds.), Arnaldi de Villanova Opera Medica Omnia VIII, Barcelona, Fundació Noguera-Universitat de Barcelona, 2023, 300 páginas, ISBN 978-84-1303-511-6